Cardiometabolic disease risk in gorillas is associated with altered gut microbial metabolism - Davison, Samuel; Mascellani Bergo, Anna; Ward, Zoe; Sackett, April; Strykova, Anna; Jaimes, José Diógenes; Travis, Dominic; Clayton, Jonathan B; Murphy, Hayley W; Danforth, Marietta D; Smith, B Katherine; Blekhman, Ran; et al. (NPJ biofilms and microbiomes, 2025)
Cardiometabolic disease is the leading cause of death in zoo apes; yet its etiology remains unknown. Here, we investigated compositional and functional microbial markers in fecal samples from 57 gorillas across U.S. zoos, 20 of which are diagnosed with cardiovascular disease, in contrast with 17 individuals from European zoos and 19 wild gorillas from Central Africa. Results show that zoo-housed gorillas in the U.S. exhibit the most diverse gut microbiomes and markers of increased protein and carbohydrate fermentation, at the expense of microbial metabolic traits associated with plant cell-wall degradation. Machine learning models identified unique microbial traits in U.S. gorillas with cardiometabolic distress; including reduced metabolism of sulfur-containing amino acids and hexoses, increased abundance of potential enteric pathogens, and low fecal butyrate and propionate production. These findings show that cardiometabolic disease in gorillas is potentially associated with altered gut microbial function, influenced by zoo-specific diets and environments.
Keywords: kardiovaskulární nemoci; Animals; Ape Diseases; zvířata v ZOO; Gorilla gorilla; Female; zvířata; feces; mužské pohlaví; Feces; Male; Animals, Zoo; Cardiovascular Diseases; Bacteria; střevní mikroflóra; ženské pohlaví; nemoci lidoopů; Gastrointestinal Microbiome